Future Prevention Strategy Based on Lessons Learned from the 2019 Peatland Fire in Tumbang Nusa Area, Indonesia - Akbar , Acep (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
The objective of this study is to formulate the concept of managing forest and land fires at the village level assuming that socio-economic, biophysical and equipment facilitation aspects greatly determine the success of fire prevention. Peatland has high capacity for carbon storage and also social-economic resource. The Tumbang Nusa area encompasses Tumbang Nusa village and Tanjung Taruna, together with a special study forest area that is managed by the Ministry of Environment and Forestry on a regional level. . The area is a peatland with peat soil depths ranging from 2 to 8 meters, which can illustrate the effects of peat fire episodes on areas with moderate to deep peat depths. The lessons learned from the 2019 fires in that area can be used to improve fire prevention tactics and management plans to prevent future surface and peat fires. Our research has demonstrated that minimizing the likelihood of a fire occurring necessitates an awareness of socioeconomic factors such as human behaviors that spark fires. This should be accompanied by an understanding of the underlying biophysical and social factors, such as peatland characteristics, involvement of fire departments, police, and the army, fuel management, local fire danger rating, fire equipment, institutional capacity, suppression response, and post-fire action. All of these learning aspects can help to strengthen village prevention efforts.